De sometimientos y rupturas: Gabriela Mistral a 80 años de su Premio Nobel. - OYARZÚN, KEMY (Nomadías)
The article focuses on the figure of Gabriela Mistral, 80 years after receiving the Nobel Prize in Literature, exploring her contributions to poetry and her views on non-binary identities, feminism, and the relationship between the individual and the nation-state. It highlights her ability to challenge patriarchal binaries and her focus on symbolic motherhood, as well as her connection to intersectional struggles encompassing gender, race, and class. The author proposes a re-reading of Mistral's work, emphasizing the importance of recognizing the diversity of subjectivities and orality in her poetry, which invites critical reflection on identity and memory in the contemporary Chilean context.